Pharmacokinetic Behavior and Pharmacokinetic/Pharmacodynamic Integration of Danofloxacin Following Single or Co-Administration with Meloxicam in Healthy Lambs and Lambs with Respiratory Infections - Mehmet Nihat Ural; Kamil Uney (MDPI AG, 2021)
The aim of this study was to determine the pharmacokinetics and pharmacodynamics of danofloxacin (DAN; 6 mg/kg) following subcutaneous administration alone or co-administration with meloxicam (MLX; 1 mg/kg) in healthy lambs and lambs with respiratory infections. The study was carried out using a total of four groups: HD (healthy; n = 6) and ID (infected; n = 7) groups who were administered DAN only, and HDM (healthy; n = 6) and IDM (infected; n = 7) groups who were administered DAN and MLX simultaneously. The plasma concentrations of DAN were determined using high-performance liquid chromatography-UV and analyzed by the non-compartmental method. DAN exhibited a similar elimination half-life in all groups, including both the healthy and infected lambs. The total clearance in the HDM, ID and IDM groups and volume of distribution in the HDM and IDM groups were significantly reduced. MLX in the IDM group significantly increased the area under the curve (AUC) and peak concentration (Cmax) of DAN compared to the HD group. The Mannheimia haemolytica, Escherichia coli, and Streptococcus spp. strains were isolated from bronchoalveolar lavage fluid samples of the infected lambs. When co-administration with meloxicam, DAN at a 6 mg/kg dose can provide optimum values of ƒAUC0-24/MIC (>56 h) and ƒCmax/MIC (>8) for susceptible M. haemolytica isolates with an MIC90 value of 0.25 µg/mL and susceptible E. coli isolates with an MIC value of ≤0.125 µg/mL.